ANALISIS SISTEM PENGENDALIAN INTERN DALAM PEMBERIAN KREDIT PADA PT. BANK PERKREDITAN RAKYAT – BINA USAHA DANA DI LARANTUKA - Aliandu, Bernadus; Londa, Yulita; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2021)
The Larantuka Dana Bina-Usaha Bank Credit Business Bank is one of the banks experiencing problems with inadequate internal control caused by a dual task between credit analysis and debt collecto / remedial, which results in problem loans. The purpose of this study was to determine internal control in granting credit to PT. Bank Perkreditan Rakyat-Bina Usaha Dana Larantuka analysis of the data used is a qualitative descriptive method. The results of this study indicate that PT. Bank Perkreditan Rakyat-Bina Usaha Dana Larantuka does not conduct regular monitoring of debtor businesses, especially those outside the city / region. In the organizational structure there is no debt collector / remidial so, the part of the credit analyst still doubles the task of becoming a debt collector / remidial. The steps taken by the bank to conduct regular monitoring of the debtor's business, there should be a debt collector / remidial so that there are no duplicate tasks performed by the credit analyst.